String vibration dampers do not reduce racket frame vibration transfer to the forearm - Li, F. X.; Fewtrell, D.; Jenkins, M. (Journal of Sports Sciences, 2005)
In this study, we examined the effect of string vibration damping devices on reducing racket frame vibration transfer to the forearm. Twenty participants volunteered to hold a tennis racket stationary in a forehand and backhand stroking position while tennis balls were fired at 20 m · s-1 towards two impact locations, the node of vibration and the dead spot. A three-way analysis of variance with repeated measures on damping condition, impact location and stroke condition was performed on the data. The resonant frequency of the hand-held racket was found to be ~120 Hz. No significant differences in amplitude of vibration at the resonant frequency were found for the wrist or the elbow when damped and non-damped impacts were compared. Impacts at the dead spot produced greater amplitudes of vibration (P < 0.01) but no interaction between impact location and string dampers was evident. The string dampers had no effect on the grip force used or the muscle electrical activity in the forearm after impact. In conclusion, we found that string dampers do not reduce the amount of racket frame vibration received at the forearm. We suggest that string dampers remain a popular accessory among tennis players because of their acoustic effects and psychological support rather than any mechanical advantage.